2017
DOI: 10.1021/acscatal.7b00494
|View full text |Cite
|
Sign up to set email alerts
|

Electrocatalytic Water Oxidation by a Copper(II) Complex of an Oxidation-Resistant Ligand

Abstract: The copper­(II) complex Cu­(pyalk)2 (pyalk = 2-pyridyl-2-propanoate) is a robust homogeneous water-oxidation electrocatalyst under basic conditions (pH > 10.4). Water oxidation occurs at a relatively low overpotential for copper of 520–580 mV with a turnover frequency of ∼0.7 s–1. Controlled potential electrolysis experiments over 12 h at 1.1 V vs NHE resulted in the formation of >30 catalytic turnovers of O2 with only ∼20% catalyst degradation. The robustness of the catalyst under fairly harsh conditions and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
127
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 153 publications
(133 citation statements)
references
References 38 publications
(15 reference statements)
2
127
0
Order By: Relevance
“…23 Vv ersus the standard hydrogen electrode) and is both thermodynamically and kinetically very unfavorable. [38][39][40] Recently,the Llobet group disclosed the synthesisofaheterotrinuclear Ru 2 Mn complex A 0 {[Ru II (tpy)] 2 (m-[Mn II (bpp) 2 ]) (OAc) 2 } 2 + [tpy = 2,2':6',2''-terpyridine, bpp = 3,5-bis(2-pyridyl)pyrazolate]. [1][2][3][4][5] During the past few decades, extraordinary efforts have been dedicated to the synthesis of manganese-based molecular complexes to mimic the structure and function of the OEC.…”
Section: Introductionmentioning
confidence: 99%
“…23 Vv ersus the standard hydrogen electrode) and is both thermodynamically and kinetically very unfavorable. [38][39][40] Recently,the Llobet group disclosed the synthesisofaheterotrinuclear Ru 2 Mn complex A 0 {[Ru II (tpy)] 2 (m-[Mn II (bpp) 2 ]) (OAc) 2 } 2 + [tpy = 2,2':6',2''-terpyridine, bpp = 3,5-bis(2-pyridyl)pyrazolate]. [1][2][3][4][5] During the past few decades, extraordinary efforts have been dedicated to the synthesis of manganese-based molecular complexes to mimic the structure and function of the OEC.…”
Section: Introductionmentioning
confidence: 99%
“…According to the previous research, the plausible catalytic mechanism for bimetallic complexes is shown in Figure . Firstly, two chlorine atoms which linked to the transition metal center were displaced by molecules of H 2 O.…”
Section: Resultsmentioning
confidence: 90%
“…With these bio‐inspired principles in mind, we report a new di‐µ‐oxo dimanganese complex of the pincer 2‐([2,2′‐bipyridin]‐6‐yl)propan‐2‐ol (bipyalkH), which acts as a strong π‐donor upon deprotonation of the alcohol. This ligand incorporates the pyridine alkoxide “pyalk” motif that we previously showed can stabilize high oxidation states in Rh and Ir and promote water‐oxidation catalysis, both with chemical oxidants and electrochemically, with Ir and Cu . We also have previously reported oxygen evolution from our low‐valent precatalyst Mn(bipyalkH)Cl 2 ( 1 , shown in Figure ) driven by KHSO 5 with retention of activity for > 160 h in unbuffered solutions.…”
Section: Introductionmentioning
confidence: 71%